2013
DOI: 10.1371/journal.pone.0079608
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hemodynamic Remodeling on the Survival of Arterialized Venous Flaps

Abstract: ObjectiveTo evaluate the effect of hemodynamic remodeling on the survival status of the arterialized venous flaps (AVFs) and investigate the mechanism of this procedure.Materials and MethodsTwo 7 x 9 cm skin flaps in each rabbit (n=36) were designed symmetrically in the abdomen. The thoracoepigastric pedicle and one femoral artery were used as vascular sources. Four groups were included: Composite skin grafts group and arterial perfusion group were designed in one rabbit; AVF group and hemodynamic remodeling g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The reasons why this strategy does not work efficiently for AVFs still remain elusive. In our previous study [10], we found that consistent venous congestion occurred in the peripheral area in a flow-through type of AVF and its hemodynamic feature is characterized as an integrated perfusion mode. Under this perfusion mode, the pressure in the central arterialized vein was high and the pressure difference between the two ends was subtle.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The reasons why this strategy does not work efficiently for AVFs still remain elusive. In our previous study [10], we found that consistent venous congestion occurred in the peripheral area in a flow-through type of AVF and its hemodynamic feature is characterized as an integrated perfusion mode. Under this perfusion mode, the pressure in the central arterialized vein was high and the pressure difference between the two ends was subtle.…”
Section: Discussionmentioning
confidence: 98%
“…This flap differs from the traditional flap because it is perfused only through the venous system [9, 10]. Several survival mechanisms regarding this kind of flaps, such as the theories of “A-V shunting”[11],“reverse flow”[12] and “capillary bypass”[13], have been brought forward, yet no consensus on its exact mechanism has been comprehensively addressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations